Aesthetics Asu Sengi Temple - Yulianto, Arif; Miranda, Bunga; Wibowo, Yudi (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
The Indonesian nation is rich in tradition and history. The historical cultural heritage spread widely from Sabang to Merauke shows that Indonesia is a great nation that has cultural historical roots since ancient times. One of the historical and cultural relics includes temples, sacred buildings which became icons of Indonesian civilization until the 17th century. The temple is an iconic building that is proof of the greatness of the Indonesian nation because it was built with high architectural calculations and technology and has a religious meaning that is rich in transcendental values. The temple is an ancient site in the form of a building that functions as a place of worship for followers of Hinduism and Buddhism. Temples are places of dharma, or burial places for certain kings, for example Kidal Temple, which is identified as the dharma of King Anusapati, while Candi Singosari is identified as the Dharma of Kertanegara as Shiva. However, in the Central Java and Yogyakarta regions, temples usually function as places of worship where Hindus and Buddhists carry out religious rituals. Nowadays, the temple functions more as a historical site that can attract tourists, both local and foreign.